Cultural openness and desire to learn in relation to ethnocultural empathy among university students in multilingual contexts - Peña-Acuña, Beatriz; Toscano-Fuentes, Carmen M.; Flor-Arasil, Patricia (Frontiers in Psychology, 2025)
IntroductionCultural openness and the desire to learn have been examined through the lens of inclusive education, particularly in relation to multicultural competencies and empathy. Empathy is recognized as a key factor in enhancing group relations. However, there is a lack of research on how these variables interact among university students in multilingual contexts.MethodsThis quantitative study surveyed 530 Spanish university students using a validated questionnaire based on the Everyday Multicultural Competencies/Revised Scale of Ethnocultural Empathy. The statistical analyses employed included Spearman’s correlation coefficient, the Mann-Whitney U test, and linear regression.ResultsResults revealed a strong positive correlation between cultural openness, desire to learn, and empathy. Statistically significant gender differences were also found in levels of empathy and openness.DiscussionThese findings suggest that training adult students in cultural openness may foster greater empathy and support inclusive education. Implementing activities that promote ethnocultural empathy in university classrooms could inform curriculum development for multicultural teacher training programs.